A Liquefaction Incident in a Waste Pass: A Case Study - F. Hassani (Canadian Institute of Mining, Metallurgy and Petroleum, 2003)
This Paper describes a sudden spill of rock waste used for backfilling from a waste pass at one of the underground mine in Canada thus causing a major failure/accident. The mine operator immediately launched a detailed investigation to understand the causes of this accident and develop procedures to prevent any recurrence of such events in future. The investigators from McGill University were invited to collaborate with the engineers at the mine to examine this accident. The events leading to the accident were studied and appropriate measurements were taken and samples of the waste material was collected for further test and analysis. The field visit and the interview of the witnesses allowed a detail documentation of the events. The sequences of events related to the incident together with the experimental results obtained in the course of the investigation is detailed. The waste material was characterised in the laboratory with regard to its behaviour in the presence of water. This information is then discussed and the failure mechanism involved in this accident is identified. The full recommendation as well as the immediate operational measures implemented by the mine to prevent future occurrence of such events are discussed and presented.